2007
DOI: 10.1128/jvi.01521-07
|View full text |Cite
|
Sign up to set email alerts
|

RNA Editing of the Human Herpesvirus 8 Kaposin Transcript Eliminates Its Transforming Activity and Is Induced during Lytic Replication

Abstract: Human herpesvirus 8 is the etiologic agent associated with Kaposi's sarcoma and primary effusion lymphoma (PEL). The K12 RNA, which produces as many as three variants of the kaposin protein, as well as a microRNA, is the most abundant transcript expressed in latent Kaposi's sarcoma-associated herpesvirus infection, and yet it is also induced during lytic replication. The portion of the transcript that includes the microRNA and the kaposin A sequence has been shown to have tumorigenic potential. Genome coordina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 57 publications
2
78
0
Order By: Relevance
“…Additional studies conducted more recently confirmed that this is indeed due to A-to-I editing at this site of the viral transcript harboring KSHV-miR-K12-10 by ADAR1 (56). Interestingly, the transcript could be processed into the viral miRNA as well as the mRNA coding for Kaposin A. A-to-I editing and consequent recoding of Kaposin A reduced its transforming activity (56). However, the significance of A-to-I editing of KSHV-miR-K12-10 RNAs remains unknown.…”
Section: Discussionmentioning
confidence: 86%
“…Additional studies conducted more recently confirmed that this is indeed due to A-to-I editing at this site of the viral transcript harboring KSHV-miR-K12-10 by ADAR1 (56). Interestingly, the transcript could be processed into the viral miRNA as well as the mRNA coding for Kaposin A. A-to-I editing and consequent recoding of Kaposin A reduced its transforming activity (56). However, the significance of A-to-I editing of KSHV-miR-K12-10 RNAs remains unknown.…”
Section: Discussionmentioning
confidence: 86%
“…Editing levels of a number of cellular and viral RNAs vary considerably, not only among different sites, but for the same site in different tissues, stages of development, and pathological settings (Bass 2002;Keegan et al 2004;Maas et al 2006;Gandy et al 2007;Cenci et al 2008;Riedmann et al 2008). As yet, the factors that determine these variations are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…KSHV pre-miR-K10 is derived from the coding region of ORF-K12 (59). Although there are several functional variants, the predominant mature miRNA in latent KSHV cells is miR-10a-3p, which can be switched to miR-10b-3p with a single point mutation during lytic replication through RNA editing (13,32,38,60,61). The ORF71-73 gene locus encodes three viral latent proteins, including vFLIP (ORF71), vCyclin (ORF72), and LANA (ORF73), that have diverse functions during viral latency.…”
Section: Determination Of the 3=utr Sequences And Polyadenylation [Pomentioning
confidence: 99%